2015
DOI: 10.4103/0973-1482.154061
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological evaluation of collagen fibers using picrosirius red stain and polarizing microscopy in oral squamous cell carcinoma

Abstract: An observable stromal change with the progression of neoplasm was evinced with picrosirius red stain in different thickness of collagens with a significant change in the arrangement from the early stage to the advanced stage according to tumorogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 0 publications
8
19
0
Order By: Relevance
“…As well as in our study other authors has used this method in various tissues to quantify collagen, for example Singh and colleagues (2012) [ 52 ] in their study about role of connective tissue stroma on biological behavior of odontogenic cysts, Geary and colleagues (2015) [ 53 ] in study of tendon repair, Manjunatha and colleagues (2015) [ 54 ] in oral squamous cell carcinoma, Alves and colleagues (2015) [ 55 ] in a study of the splenic collagen polymorphism, and many others.…”
Section: Discussionmentioning
confidence: 80%
“…As well as in our study other authors has used this method in various tissues to quantify collagen, for example Singh and colleagues (2012) [ 52 ] in their study about role of connective tissue stroma on biological behavior of odontogenic cysts, Geary and colleagues (2015) [ 53 ] in study of tendon repair, Manjunatha and colleagues (2015) [ 54 ] in oral squamous cell carcinoma, Alves and colleagues (2015) [ 55 ] in a study of the splenic collagen polymorphism, and many others.…”
Section: Discussionmentioning
confidence: 80%
“…They concluded that the collagen fibers were more disorganized in moderately to poorly differentiated OSCC. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have studied the birefringence property of collagen fibers,[ 3 4 5 ] but studies which evaluated the other aspects of collagen fibers (orientation, arrangement, density, packing and area fraction) in OSCC are only a handful. [ 6 7 8 9 10 ] Apart from collagen fibers, the elastic fibers also are an integral component of the extracellular matrix (ECM). As per the literature, there is an interaction between the tumor cells and elastic fibers, but its effect on the progression of carcinoma is questionable.…”
Section: Introductionmentioning
confidence: 99%
“…OSCC is composed of two distinct components: (a) the malignant epithelial cells; and (b) the stroma in which they are dispersed . One of the major aspects of tumor cell invasion and metastasis is the interaction between cancer cells and the extracellular matrix (ECM) component . The ECM is composed of a ground substance made up of proteoglycans, glycoproteins, and water, and the fibrous component, including collagen and elastic fibers .…”
Section: Introductionmentioning
confidence: 99%